2005
DOI: 10.1021/bi0473298
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Aminoglycosides' RNA Binding Proclivity and Their Antiplasmid Effect on an IncB Plasmid

Abstract: Bacteria routinely become resistant to antibiotics through the uptake of plasmids that encode resistance-mediating proteins. Such plasmid-based resistance is seen extensively in clinical settings and has been documented for a wide variety of bacterial infections from both Gram-positive and Gram-negative organisms. We recently reported that a small molecule could be used to mimic a natural process of plasmid elimination, called plasmid incompatibility, and that the addition of this compound causes elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 86 publications
0
31
0
2
Order By: Relevance
“…The exploitation of the mechanisms of plasmid incompatibility has been explored (37,139,153). In this case, the plasmid replication machinery is an obvious target, for instance using compounds able to reduce the intracellular levels of RepA replicase.…”
Section: Promiscuity Inhibitors (I) Inhibitors Of Interbacterial Dismentioning
confidence: 99%
See 1 more Smart Citation
“…The exploitation of the mechanisms of plasmid incompatibility has been explored (37,139,153). In this case, the plasmid replication machinery is an obvious target, for instance using compounds able to reduce the intracellular levels of RepA replicase.…”
Section: Promiscuity Inhibitors (I) Inhibitors Of Interbacterial Dismentioning
confidence: 99%
“…In this case, the plasmid replication machinery is an obvious target, for instance using compounds able to reduce the intracellular levels of RepA replicase. These levels are determined by its interaction with a small RNA, RNAI, whose conformation can be altered by drugs, such as apramycin, at least in incompatibility IncB systems (139). An apparent limitation to such an approach is the possible rapid emergence of plasmid elimination-resistant mutants by mutational changes in the Rep sequences.…”
Section: Promiscuity Inhibitors (I) Inhibitors Of Interbacterial Dismentioning
confidence: 99%
“…It has been shown that aminoglycosides specifically bind to the bacterial ribosomal RNA and inhibit the bacterial protein biosynthesis [1]. Based on the specific interaction with RNA molecules, many applications such as anti-HIV infection [2,3] and anti-plasmid [4,5], are continuously investigated [6ϳ8]. Thus, the creation of a library for structurally diverse aminoglycoside molecules is strongly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the pET-28 (b) plasmid into the above E.coli strain reduced lacZ expression regardless of IPTG addition (Fig. 6, 5 th and 6 th bar) due to incompatibility as both plasmids, pDL and pET, harbor same replication origin (Thomas et al, 2005 (Fujita et al, 2008) suggesting that the increased amounts of CbbX (nuc) did not affect the transcription of RuBisCO operon. If CbbX (nuc) functions as a modifier of CbbX (pt) repressor in vivo in C. merolae, increased CO 2 concentration should affect expression of the RuBisCO operon on the plastid genome by modifying of CbbX (pt) repressor function.…”
Section: Determination Of Transcription Start Site Of Rbclmentioning
confidence: 97%